Muhammad Bin Abdul Kadir (Haji Sulung): Perjuangan dan Pengabdiannya - Jeh-Ngoh, Abdulfatta (Studi Multidisipliner: Jurnal Kajian Keislaman, 2021)
Muhammad bin Abdul Kadir bin Zainal Abidin bin Ahmad (Haji Sulong) (1895-1954) was an Islamic scholar, leader of the Islamic movement and Malay nationalism in the fields of education, religion and socio-politics. He was also included in the group of ulama who led religious reform and nationalist movements in Malaya and Indonesia in the first decades of the 20th century. In the field of religion, there are two important activities that have been carried out by Haji Sulong, namely teaching activities by preaching and his efforts to defend Sharia law. Haji Sulong teaches religion by preaching throughout Pattani. After seeing the support that began to grow in the community, then Haji Sulong began to introduce the idea of an educational institution in a modern form to the community, namely Madrasah al-Maarif al-Wataniah could be established. Haji Sulong's struggle in the political field by being involved in the struggle to improve the fate of Patani Muslims. A struggle that perfected his life career even though this effort was unacceptable to the Thai government, but made a big contribution to the struggle of the Patani Muslims in the future